Arrhythmia Burden in Elderly Patients With Severe Aortic Stenosis as Determined by Continuous Electrocardiographic Recording. Issue 5 (3rd February 2015) - Urena, Marina; Hayek, Salim; Cheema, Asim N.; Serra, Vicenç; Amat-Santos, Ignacio J.; Nombela-Franco, Luis; Ribeiro, Henrique B.; Allende, Ricardo; Paradis, Jean-Michel; Dumont, Eric; Thourani, Vinod H.; Babaliaros, Vasilis; et al.
<x xml:space="preserve">Abstract</x> Background— This study sought to evaluate the prevalence of previously undiagnosed arrhythmias in candidates for transcatheter aortic valve replacement (TAVR) and to determine the impact on therapy changes and arrhythmic events after the procedure. Methods and Results— A total of 435 candidates for TAVR underwent 24-hour continuous ECG monitoring the day before the procedure. Newly diagnosed arrhythmias were observed in 70 patients (16.1%) before TAVR: paroxysmal atrial fibrillation (AF)/atrial tachycardia (AT) in 28, advanced atrioventricular block or severe bradycardia in 24, nonsustained ventricular tachycardia in 26, and intermittent left bundle-branch block in 3 patients. All arrhythmic events but one were asymptomatic and led to a therapy change in 43% of patients. In patients without known AF/AT, the occurrence of AF/AT during 24-hour ECG recording was associated with a higher rate of 30-day cerebrovascular events (7.1% versus 0.4%; P=0.030). Among the 53 patients with new-onset AF/AT after TAVR, 30.2% had newly diagnosed paroxysmal AF/AT before the procedure. In patients who needed permanent pacemaker implantation after the procedure (n=35), 31.4% had newly diagnosed advanced atrioventricular block or severe bradycardia before TAVR. New-onset persistent left bundle-branch block after TAVR occurred in 37 patients, 8.1% of whom had intermittent left bundle-branch block before the procedure. Conclusions— Newly diagnosed arrhythmias were observed in approximately a fifth of TAVR candidates, led to a higher rate of cerebrovascular events, and accounted for a third of arrhythmic events after the procedure. This high arrhythmia burden highlights the importance of an early diagnosis of arrhythmic events in such patients to implement the appropriate therapeutic measures earlier.